ANALYSIS OF THE APPLICATION OF SIAPIK IN THE PREPARATION OF FINANCIAL REPORTS BASED ON SAK EMKM TO IMPROVE THE ACCOUNTABILITY OF THE SALSA BEAUTY SALON UMKM - Duwi Rahayu; Tarin Achuistina (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to analyze the application of the Financial Information Recording Application Information System (SIAPIK) in preparing financial reports based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) to improve accountability in the Salsa Beauty House Salon MSME. Method: This study examines how business actors utilize the SIAPIK application in the process of recording and preparing financial reports so that the resulting information is more systematic, accurate, and reliable. This study uses a qualitative approach with data collection techniques through observation and interviews with business actors. Results: The results show that Salsa Beauty House Salon has met the criteria for presenting financial reports according to SAK EMKM. However, there are still several obstacles in the recording process, especially related to the limited human resources who have the ability to prepare financial reports optimally using the SIAPIK application. Novelty: This study analyzes the application of the SIAPIK information system in preparing SAK EMKM-based financial reports to improve accountability in the Salsa Beauty House Salon MSME.